Supramolecular systems and their connection with metal–organic structures - Cué-Sampedro, Rodrigo; Sánchez-Fernández, José Antonio (Frontiers in Chemistry, 2024)
Supramolecular structures with specific applications are a pillar in several areas of science. Thus, from a contemporary point of view, there are several reasons to embrace a systematic order of the supramolecular concept itself. First, the structuring of a supramolecular material seems safer now than it did decades ago. Second, the interactions of metal–organic frameworks (MOFs) and supramolecular chemistry and, conversely, supramolecularity to assemble MOFs and create efficient complex systems in multiple cutting-edge applications are an image to be safeguarded. Third, perhaps we should simply limit ourselves to considering how researchers in these fields have attempted to correlate the notion of supramolecular systems by linking self-assembly considerations. In any case, these topics present advantages to optimize innovative geometries that are useful to highlight significant practical applications. This review covers a general introduction to MOFs and supramolecularity, the key unit of the study presented here, followed by a survey of recent advances in confined space chemistry, the relationships of MOFs with supramolecular structures, and the synthesis electrochemistry of MOFs and switchable MOFs to obtain a greater understanding of structure–property relationships. To conclude, some future perspectives on this promising and plausible field of science will be mentioned.